Effect of first aid training on teams from special education schools - Jackeline Gonçalves Brito; Inês Pereira de Oliveira; Christine Baccarat de Godoy; Ana Paula dos Santos Jesus Marques França (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: Analyze the effect of first aid training on the knowledge of multidisciplinary teams from special education schools, in school accidents. Methods: A quasi-experimental, before-and-after study with a single comparison group. Descriptive statistics and McNemar's test were used to evaluate the effect of the intervention. Results: This study had the participation of 162 higher education professionals, predominantly teachers (82.1%), female (97.5%), aged over 40 (69.2%). An increase in correct answers was observed, with statistical significance (≤0.05), especially in proper handling in case of fall with traumatic brain injury, electric shock, and burn due to hot liquid (98.1%, 98.1% and 96.9% of proper response, respectively). Conclusions: First aid training for child accidents, through content exhibition, in a dialogical and practical way, proved to be efficient for multidisciplinary teams from special education schools for people with disabilities.